Synthesis, characterization, and antiplasmodial efficacy of sulfonamide‐appended [1, 2, 3]‐triazoles. (28th January 2020) - Batra, Neha; Rajendran, Vinoth; Wadi, Ishan; Lathwal, Ankit; Dutta, Roshan Kumar; Ghosh, Prahlad C.; Gupta, Rinkoo D.; Nath, Mahendra
Abstract: A series of benzenesulfonamide‐appended [1, 2, 3]‐triazole hybrids was synthesized by using [3 + 2] cycloaddition of primary, secondary, and tertiary sulfonamide azides with various phenoxymethylacetylenes under click reaction conditions. After structural characterization, the compounds were subjected to in‐silico absorption, distribution, metabolism, excretion and toxicity (ADMET) screening to evaluate their drug‐likeness and other pharmacokinetic parameters. Furthermore, their in vitro antiplasmodial potential was assessed against Plasmodium falciparum (3D7) strain, and some of the synthesized compounds displayed promising antimalarial potency. On cytotoxicity evaluation using MTT cell viability assay, the most active candidate N ‐(4, 6‐dimethylpyridin‐2‐yl)‐4‐(4‐(4‐nitrophenoxy)methyl)‐1 H ‐[1, 2, 3]‐triazol‐1‐yl)benzenesulfonamide (14 ; IC50 6.2 μg/mL) demonstrated CC50 7.5 μg/mL against human hepatocarcinoma (HUH‐7) cells. Abstract :